Análisis del impacto de un sistema para la gestión de asistencias docentes en FAFI. - Fuentes Zambrano, Kleber José (2025)
Today, higher education institutions face great challenges related to the modernization of their administrative and academic processes. One of the so-called critical areas is the management of teaching assistance, which forms a fundamental mechanism to guarantee the effectiveness of the educational service. According to this perspective, the need arises to create an innovative system for the management of teaching assistance that not only allows the resolution of current problems, but also incorporates modern technological tools capable of preparing the FAFI towards a cutting-edge digital administration model. This type of system will not only solve operational needs, but will also favor the performance of international schemes in educational management, placing the FAFI with digital innovation standards in the academic area. This case study proposes the use of cutting-edge technological tools, such as biometrics for attendance control and registration, and interactive panels for decision making supported by secure data.